Imports, Entry, and Competition Law as Market Disciplines - Kee, Hiau Looi; Hoekman, Bernard (World Bank, Washington, DC, 2014)
Since the early 1990s numerous countries have adopted or strengthened competition legislation. Kee and Hoekman investigate the impact of competition law on industry markups over time and across a large number of countries. They find both domestic and foreign competition to be major sources of market discipline in concentrated markets, but that the direct effect of competition law is insignificant. However, once allowance is made for the endogeneity of both domestic competiton (number of firms) and the adoption of a competition law, the authors find that competition laws have an indirect effect on equilibrium markups by promoting a larger number of domestic firms.